2016
DOI: 10.1007/s10964-016-0457-7
|View full text |Cite
|
Sign up to set email alerts
|

Family Structure, Maternal Dating, and Sexual Debut: Extending the Conceptualization of Instability

Abstract: Family structure influences the risk of early onset of sexual intercourse. This study proposes that the family structures associated with risk-single-mother, step-parent, and cohabiting-influence early sexual debut due to family instability, including shifts in family structure and maternal dating, which can undermine parental control and transmit messages about the acceptability of nonmarital sex. Previous research has not considered maternal dating as a component of family instability, assuming single mother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 67 publications
1
14
1
1
Order By: Relevance
“…In the same way, the family, as a basis for the establishment of social bonds, continues to play an important role for teenagers, even if they naturally move away from family ties and strengthen their friendship bonds 21 . Although the literature pointed out an unstable family structure as a risk factor for early sexual initiation in adolescents and for motherhood 22 , the present study was not able to detect such effect. This result maybe implies that trusting not only on parents but, specially, on extended family had contributed for the protective effect on adolescent motherhood.…”
Section: Discussioncontrasting
confidence: 96%
“…In the same way, the family, as a basis for the establishment of social bonds, continues to play an important role for teenagers, even if they naturally move away from family ties and strengthen their friendship bonds 21 . Although the literature pointed out an unstable family structure as a risk factor for early sexual initiation in adolescents and for motherhood 22 , the present study was not able to detect such effect. This result maybe implies that trusting not only on parents but, specially, on extended family had contributed for the protective effect on adolescent motherhood.…”
Section: Discussioncontrasting
confidence: 96%
“…Neither parent–child relationship quality nor material disadvantage show evidence of mediating the (nonsignificant) link between parental separation and adult partnership status. There were no significant differences in the mediation by gender in Vargas et al () or Zito and De Coster (). This suggests that the stress mediation pathway is similar for boys and girls.…”
Section: Resultsmentioning
confidence: 81%
“…Three studies found mediation for some of the transitions or some of the outcomes but not all (Bachman et al, ; Sun & Li, ; Vargas, Roosa, Knight, & O'Donnell, ). The overwhelming majority of the studies with family functioning and parenting mediating variables, however, found no evidence that these variables were mediators during adolescence (Bachman et al, ; Krohn, Penly Hall, & Lizotte, ; Langenkamp & Frisco, ; Schroeder et al, ; Shaff et al, ; Walper et al, ; Zito, ; Zito & De Coster, ). Finally, no studies suggested that parent functioning was a consistent mediator: Bachman et al () found that parents' psychological distress was a mediator only for cohabiting relationships lasting at least 2 years; and neither Bachman et al () nor Zito () found any mediation effect by parent functioning.…”
Section: Resultsmentioning
confidence: 99%
“…The quality of family support may influence the occurrence of pregnancy in adolescence. For example, studies indicate that the earlier an adolescent initiates the sex life, the greater the likelihood of becoming pregnant at this stage of development (Maranhão et al 2017), and, in turn, the early sexual initiation is related to factors of the family instability, such as maternal dating in single-parent female families and permissive parental educational practices (Zito and De Coster 2016).…”
Section: Family and Relational Aspectsmentioning
confidence: 99%